Children's Character Education through Local Wisdom-Based Stories in Indonesia - Miranda, Mega; Ambarwati, Ari; Badrih, Moh (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Children's character education is one of the important focuses in forming the next generation who are moral, resilient, and have integrity. This study analyzes the implementation of character education values through children's stories based on local wisdom. Stories based on local wisdom have great relevance in the context of today's education. , because it is able to provide contextual learning, rooted in national culture, and relevant to global challenges. This study aims to identify the character values contained in children's stories, and explore how local wisdom can enrich the learning process and character formation of children. By using qualitative approach and content analysis, this study analyzes children's stories that raise the theme of local wisdom from various regions in Indonesia. The results of the study show that children's stories based on local wisdom can be an effective means to instill values such as honesty, cooperation, responsibility, love of the homeland, and environmental awareness. In addition, these stories are relevant to be used as interactive and inspiring teaching materials in school learning or used for learning at home. This helps to form a strong character and a positive sense of identity. By integrating these values into education, children can learn to appreciate tradition while developing good attitudes in everyday life.